HYDROGEN EHERGETICS IN THE FIELD OF ENERGY - Xalilova, Feruza Abdulvosiyevna (Educational Research in Universal Sciences, 2023)
The article describes today’s widespread use of hydrogen energy in the field of energy, the fields of hydrogen application, the development of hydrogen energy technologies, and the possibilities of continuous energy supply to our country’s economy and population.